SenseWear Armband and Stroke: Validity of Energy Expenditure and Step Count Measurement during Walking - Patricia J. Manns; Robert G. Haennel (Stroke Research and Treatment)
The purpose of this study was to test the validity of the SenseWear Pro Armband (SWA) for the measurement of energy expenditure (EE) and step count against a criterion in persons with stroke. Twelve participants with chronic stroke (mean age 64.2±10.4 years; mean gait speed 0.67±0.25 m/sec) completed two trials of a six-minute walk test, while wearing a SenseWear Armband (SWA) on each arm and being continuously monitored using a portable metabolic cart. Agreement between estimates of energy expenditure from the SWA and the metabolic cart was fair for the armband on the hemiplegic arm (intraclass correlation cefficient (ICC)=0.586) and good for the armband on the unaffected arm (ICC=0.702). Agreement between the SWA estimate of step count, and step count as measured by the Step Activity Monitor was poor (ICC<0.352), with significant underestimation by the SWA. Our results show that, for these moderately impaired persons with stroke, the SWA should be used with caution for the measurement of energy expenditure and should not be used to measure step count.